Granzymes and Caspase 3 Play Important Roles in Control of Gammaherpesvirus Latency - Loh, Joy (American Society for Microbiology, 2004)
Gammaherpesviruses can establish lifelong latent infections in lymphoid cells of their hosts despite active antiviral immunity. Identification of the immune mechanisms which regulate gammaherpesvirus latent infection is therefore essential for understanding how gammaherpesviruses persist for the lifetime of their host. Recently, an individual with chronic active Epstein-Barr virus infection was found to have mutations in perforin, and studies using murine gammaherpesvirus 68 (γHV68) as a small-animal model for gammaherpesvirus infection have similarly revealed a critical role for perforin in regulating latent infection. These results suggest involvement of the perforin/granzyme granule exocytosis pathway in immune regulation of gammaherpesvirus latent infection. In this study, we examined γHV68 infection of knockout mice to identify specific molecules within the perforin/granzyme pathway which are essential for regulating gammaherpesvirus latent infection. We show that granzymes A and B and the granzyme B substrate, caspase 3, are important for regulating γHV68 latent infection. Interestingly, we show for the first time that orphan granzymes encoded in the granzyme B gene cluster are also critical for regulating viral infection. The requirement for specific granzymes differs for early versus late forms of latent infection. These data indicate that different granzymes play important and distinct roles in regulating latent gammaherpesvirus infection.